Correlation Between Nutritional Status and Risk of Anemia in Students at SDN Cijagra 1 Bojongsoang, Bandung Regency - Gianita Lestari; Zakiah Zahira; Maisaroh Noor Amilia (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Anemia is a global health problem that can affect the growth and development of school-aged children. Nutritional status is suspected to be associated with the incidence of anemia, but this relationship requires further study. This study aims to analyze the correlation between nutritional status and the risk of anemia in students of SDN Cijagra 1 Bojongsoang, Bandung Regency. This study used an observational analytical design with a cross-sectional approach. The sample consisted of 69 students aged 10-12 years old who were selected using purposive sampling based on inclusion and exclusion criteria. Nutritional status was measured by assessing weight and height to determine Body Mass Index (BMI), while hemoglobin levels were measured using the POCT (Point of Care Testing) method. Due to non-normal data distribution, bivariate analysis was performed using Spearman’s rank correlation test. The majority of students had good nutritional status (65%) and were free of anemia (94%). A small proportion experienced mild anemia (3%) and moderate anemia (3%), with no cases of severe anemia. Statistical analysis showed a correlation coefficient of -0.118 with a p-value of 0.335, indicating a very weak and statistically insignificant relationship between nutritional status and the incidence of anemia (p>0.05). The results of this study indicate that good nutritional status is not always the primary factor in preventing anemia in elementary school children. Other factors such as diet, infections, and genetic conditions likely play a more significant role in the incidence of anemia. It can be concluded that there was no significant correlation between nutritional status and the risk of anemia in students at SDN Cijagra 1 Bojongsoang, Bandung Regency. Interventions in the form of nutrition education regarding iron intake and regular health check-ups are still needed to prevent anemia.